Infant progressive colonic stenosis caused by antibiotic-related Clostridium difficile colitis - a case report and literature review - Xiaolong Xie; Bo Xiang; Yang Wu; Yiyang Zhao; Qi Wang; Xiaoping Jiang (BMC, 2018)
Abstract Background Colonic stenosis is a rare cause of pediatric intestinal obstruction. The root cause underlying colonic stenosis is unclear and there is no fixed operation. Case presentation We reported on a male infant with progressive colonic stenosis caused by antibiotic-related colitis. The infant was admitted to our hospital with pneumonia but developed progressive abdominal distension and diarrhea following antibiotic treatment with meropenem. Initial testing of stool culture showed a Clostridium difficile infection. Additional testing with barium enema imaging showed stenosis at the junction of the sigmoid and descending colon at first and another stenosis occurred at the right half of the transverse colon 3 weeks later. Staged surgical treatment was performed with primary resections of the two parts suffering stenosis, ileostomy, and secondary intestinal anastomosis. A pathological exam then confirmed the diagnosis of colonic stenosis and the patient had an uneventful recovery and has been recovering well as evidenced by the 1-year follow-up. Conclusions Based on a review of the literature and our case report, we found that progressive colonic stenosis caused by colitis due to antibiotic-related Clostridium difficile infection is rare in infants. Infants with colitis and repeated abdominal distention, vomiting, and constipation should be treated with the utmost caution and screened. Despite this, clinical manifestations depended on the severity of the stenosis. Barium enema, colonoscopy, laprascopy or laparotomy and colonic biopsy are helpful for diagnosis and differential diagnosis. While both one-stage and multiple-stage operations are feasible, a staged operation should be used for multiple colonic stenoses.